Exposure to nuclear antigens contributes to the induction of humoral autoimmunity during tumour necrosis factor alpha blockade. Issue 6 (14th July 2008) - Cantaert, T; De Rycke, L; Mavragani, C P; Wijbrandts, C A; Niewold, T B; Niers, T; Vandooren, B; Veys, E M; Richel, D; Tak, P P; Crow, M K; Baeten, D
Abstract : Objective: Type I interferons and apoptotic particles contribute to antinuclear autoimmunity in experimental models. This study assessed whether similar mechanisms contribute to break peripheral B-cell tolerance in humans by studying the induction of antinuclear antibodies by tumour necrosis factor blockade in spondyloarthritis. Methods: 40 spondyloarthritis patients treated with infliximab or etanercept and 20 renal cell carcinoma patients treated with sorafenib were studied. Serum antinucleosome IgM and nucleosomes were measured by ELISA. Type I interferon serum activity was measured using a functional reporter cell assay. Synovial apoptosis was assessed by terminal transferase nick end-labelling (TUNEL) assay and anti-active caspase-3 immunostaining. Complement was measured by nephelometry. Results: Despite a similar clinical improvement and reduction of synovial inflammation, antinucleosome IgM were induced by infliximab but not etanercept. This induction did not correlate with type I interferon activity, which was transiently downmodulated by infliximab but persistently upregulated by etanercept. In contrast, antinucleosome IgM levels did correlate with serum nucleosome levels, which were significantly upregulated by infliximab but not by etanercept treatment. This increase in serum nucleosome levels was not directly related to massive cell death, but rather to a decrease of complement 3 and 4 serum levels during infliximab treatment. Conclusion: Infliximab and etanercept have a differential effect on both type I interferon activity and nucleosome levels. Only elevated serum nucleosomes relate to the induction of antinucleosome antibodies after infliximab treatment.